The Role of Auxin-Ethylene Crosstalk in Orchestrating Primary Root Elongation in Sugar Beet - Abts, Willem; Vandenbussche, Bert; De Proft, Maurice P.; Van de Poel, Bram (Frontiers in Plant Science, 2017)
It is well established in Arabidopsis and other species that ethylene inhibits root elongation through the action of auxin. In sugar beet (Beta vulgaris L.) ethylene promotes root elongation in a concentration dependent manner. However the crosstalk between ethylene and auxin remains unknown during sugar beet seedling development. Our experiments have shown that exogenously applied auxin (indole-3-acetic acid; IAA) also stimulates root elongation. We also show that auxin promotes ethylene biosynthesis leading to longer roots. We have further demonstrated that the auxin treatment stimulates ethylene production by redirecting the pool of available 1-aminocyclopropane-1-carboxylic acid (ACC) towards ethylene instead of malonyl-ACC (MACC) resulting in a prolonged period of high rates of ethylene production and a longer root. On the other hand we have also shown that endogenous IAA levels were not affected by an ACC treatment during germination. All together our findings suggest that the general model for auxin-ethylene crosstalk during early root development, where ethylene controls auxin biosynthesis and transport, does not occur in sugar beet. On the contrary, we have shown that the opposite, where auxin stimulates ethylene biosynthesis, is true for sugar beet root development.